LncRNA H19/miR‐675 axis represses prostate cancer metastasis by targeting TGFBI. (21st July 2014) - Zhu, Miaojun; Chen, Qin; Liu, Xin; Sun, Qian; Zhao, Xian; Deng, Rong; Wang, Yanli; Huang, Jian; Xu, Ming; Yan, Jianshe; Yu, Jianxiu
<x xml:space="preserve">Abstract</x> Prostate cancer is a leading cause of cancer‐related mortality in men worldwide and there is a lack of effective treatment options for advanced (metastatic) prostate cancer. Currently, limited knowledge is available concerning the role of long non‐coding RNAs in prostate cancer metastasis. In this study, we found that long non‐coding RNA H19 (H19) and H19‐derived microRNA‐675 (miR‐675) were significantly downregulated in the metastatic prostate cancer cell line M12 compared with the non‐metastatic prostate epithelial cell line P69. Upregulation of H19 in P69 and PC3 cells significantly increased the level of miR‐675 and repressed cell migration; however, ectopic expression of H19 in M12 cells could not increase the level of miR‐675 and therefore had no effect on cell migration. Furthermore, we found that the expression level of either H19 or miR‐675 in P69 cells was negatively associated with the expression of transforming growth factor β induced protein (TGFBI), an extracellular matrix protein involved in cancer metastasis. Dual luciferase reporter assays showed that miR‐675 directly bound with 3′UTR of TGFBI mRNA to repress its translation. Taken together, we show for the first time that the H19–miR‐675 axis acts as a suppressor of prostate cancer metastasis, which may have possible diagnostic and therapeutic potential for advanced prostate cancer.